High Pulse: Exploring the Exhibit Features of a Collaborative, Whole-Body Exhibition for Experiential Learning in Science Centers - Lykke, Marianne; Skov, Mette; Jantzen, Christian (Frontiers in Education, 2021)
This research explored how collaborative, whole-body exhibits effect science learning in informal out-of-school settings. Specifically, the study investigated how exhibit features guided visitors to engage actively in experiential exploration of the exhibition topics, and how exhibit features guided visitors to make sense of the interaction and transform experiences into knowledge. The study took place at a science center in Denmark. The context was the PULSE exhibition consisting of eight individual exhibits that aimed at facilitating discussions on the importance of bodily activities for physical and social well-being. Together the exhibits formed the traditional parts of a family home and core family activities, e.g., a kitchen for cooking. Each exhibit built on experiencing through physical activity and revolved around one or several biological phenomena, e.g., balance, coordination, suppleness. All exhibits were designed for group interaction. The study explored the visitors’ experiences with the exhibition using data from walking interviews with 34 visitor groups comprising a total of 108 visitors. Each exhibit was composed of a set of exhibit features, and the study analyzed how these features supported the experiential learning. The findings showed that the whole-body activities and group collaboration constituted the greatest motivation to participate in the exhibition and thereby explore the themes of the exhibition. As regard the visitors’ learning most groups expressed the joy of physical movement, group work and need of strategy planning to carry out the activities in their conversations, whereas only a few groups seemed to perceive and reflect on the biological phenomena presented. Due to the physically demanding activities and the required social collaboration, the visitors were not able to engage in in-depth explorations of the exhibition’s scientific themes. In some exhibits where scientific information was incorporated naturally in the activity through interactive videos, the visitors talked about the themes as a natural part of the activity. Altogether, the findings have been used to outline a set of design principles for collaborative whole-body exhibits.